2006
DOI: 10.1175/mwr3158.1
|View full text |Cite
|
Sign up to set email alerts
|

Singular Vector Analysis for Atmospheric Chemical Transport Models

Abstract: The singular vectors of a chemical transport model are the directions of maximum perturbation growth over a finite time interval. They have proved useful for the estimation of error growth, the initialization of ensemble forecasts, and the optimal placement of adaptive observations. The aim of this paper is to address computational aspects of singular vector analysis for atmospheric chemical transport models. The distinguishing feature of these models is the presence of stiff chemical interactions. A projectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Building on the early variational approach (Lorenc, 1986;Le Dimet and Talagrand, 1986;Talagrand and Courtier, 1987), the 4D-Var framework represents the current state of the art in meteorological (Courtier et al, 1994;Rabier et al, 2000) and chemical (Elbern et al, 2000;Elbern and Schmidt, 2001;Liao et al, 2005;Sandu et al, 2003;Sandu et al, 2005a;Sandu, 2006;Segers, 2002) data assimilation. Ensemble Kalman filter (EnKF) data assimilation (Evensen, 1994(Evensen, , 2003Burgers et al, 1998) has recently attracted considerable interest in the context of NWP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the early variational approach (Lorenc, 1986;Le Dimet and Talagrand, 1986;Talagrand and Courtier, 1987), the 4D-Var framework represents the current state of the art in meteorological (Courtier et al, 1994;Rabier et al, 2000) and chemical (Elbern et al, 2000;Elbern and Schmidt, 2001;Liao et al, 2005;Sandu et al, 2003;Sandu et al, 2005a;Sandu, 2006;Segers, 2002) data assimilation. Ensemble Kalman filter (EnKF) data assimilation (Evensen, 1994(Evensen, , 2003Burgers et al, 1998) has recently attracted considerable interest in the context of NWP.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable progress has been made recently in the development of variational tools for chemical data assimilation (Liao et al, 2005;Sandu et al, 2003;Sandu et al, 2005a;Sandu, 2006). However, compared with NWP and ocean applications, little work has been done to date on assimilating chemical observations using nonlinear ensemble filters.…”
Section: Introductionmentioning
confidence: 99%
“…The real setting presented several challenges and difficulties: in particular, filter divergence, and limitation of the ensemble spread by the positivity constraints of the model. Additionally, a comparison with 4D-Var (Courtier et al, 1994;Rabier et al, 2000;Liao et al, 2006;Sandu et al, 2005;Chai et al, 2006) was undertaken in order to assess EnKF's effectiveness against a well-proven technique. The results indicated that 4D-Var and EnKF produced results of similar quality.…”
Section: Introductionmentioning
confidence: 99%
“…An autoregressive model of background errors [74,25] was used, which accounted for spatial correlations, distance decay, and chemical lifetime.…”
Section: Results With Ensemble-based Chemical Data Assimilationmentioning
confidence: 99%
“…In [74] we studied the computation of singular vectors for atmospheric chemical transport models. The study found that singular vectors are shaped by both the meteorology and chemistry.…”
Section: Singular Vectors and Maximal Error Growthmentioning
confidence: 99%